A irrigação no mundo e no Brasil - Muniz Nery, J (Revista Ceres, 1940)
This paper summarizes data relative to irrigation system existent in various countries and cites examples of remarkable results attributable to irrigation practices. A study of the national situation as related to the hydrological regime demonstrates the urgent necessity for irrigation of Brazilian lands. A project in water management, recently developed at the Minas Gerais State University of Agriculture and Veterinary Sciences, Viçosa, is presentend in complementary form. In view of the present hydrological situacion, it is use- less to hope for a more_convenient distribution of precipita- tion in the near future. The only solution is the installation ol irrigation equipment, to provide necessary water during the periodic droughts and Indian summer. With the aid of irrigation, man can harness the land, with compensatory results. Fertil irrigation not only insures extraordinary growth, but also makes possible cultivation of the land during all seasons of the year, with corresponding economic benefits. The Brasilian farmer must not expect governamental forces to alleviate this entire situation. He, with his own interests in view, should begin irrigation of his fields, not forgetting however, that such a projectis a technical under- taking, initially expensive but highly compensatory.